PHYSICOCHEMICAL ANALYSIS OF ANALOG RICE MADE FROM KEPOK BANANA (MUSA PARADISIACA FORMA TYPICAL) FLOUR WITH ADDED OF SAGO STARCH. - Hiola, Nur Pratiwi; Tahir, Muh; Limonu, Marleni (Jambura Journal of Food Technology, 2023)
This research aims at finding out the proximate composition, water absorption, and bulk density of analog rice made from kepok banana flour with sago starch addition. This research applies a completely randomized design with a single factor and five treatments, which comprise three repetitions. This research is conducted for two months in the Agricultural product laboratory of Poligon (Politeknik Gorontalo) and at Manado Industrial Research Center. The first stage is the raw material preparation of analog rice, which includes the manufacturing process of kepok banana flour. Techniques of data analysis are the statistical tests of analysis of variance (ANOVA) at the level of Î± = 5%, and Ms. Excel 2007. Data analysis with significant differences is tested using Duncan's multiple range test (DMRT) method and the SPSS 16.0 application. Findings reveal that analog rice made from kepok banana flour with added of sago starch has a significant effect on water content, dust content, fat content, protein content, carbohydrate content, and water absorption. bulk density that ranges from 4.25-5.47%, 1.92-2.34%, 82.66-79.18%, 1.75-0.89%, 82.36-85.07%, 68-7-76.2%, and 0.5-0.6 g/cm3 respectively.